2016
DOI: 10.1017/npt.2016.9
|View full text |Cite
|
Sign up to set email alerts
|

From skill translation to devaluation: the de-qualification of migrants in Turkey

Abstract: Within the context of the transformation of Turkey from a country of emigration to an immigration and transit country, the migration scene is becoming more heterogeneous, with both the formal and informal labor markets being increasingly internationalized. This paper focuses on de-qualification, defined as migrants taking on jobs that do not match their skills, which is a neglected issue within the migration literature on Turkey with the potential for further research. Based on open-ended interviews and partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…At a micro/individual level, such studies enrich knowledge in their attempts to better understand the conditionalities, mechanisms and impacts of immigrants' over-education, as well as the (non-)utilisation of their human capital, and more broadly, the international migration movements of highly-skilled persons (e.g. Rye and Andrzejewska, 2010;Aure, 2013;Raghuram and Kofman, 2004;Webb, 2015;Sert, 2016;Garrido and Codóc, 2017).…”
Section: Data and Methodological Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…At a micro/individual level, such studies enrich knowledge in their attempts to better understand the conditionalities, mechanisms and impacts of immigrants' over-education, as well as the (non-)utilisation of their human capital, and more broadly, the international migration movements of highly-skilled persons (e.g. Rye and Andrzejewska, 2010;Aure, 2013;Raghuram and Kofman, 2004;Webb, 2015;Sert, 2016;Garrido and Codóc, 2017).…”
Section: Data and Methodological Approachmentioning
confidence: 99%
“…Viewed from another angle, innate qualities, personality traits, newly adopted capabilities and experience of a local culture (localised knowledge) are highlighted (McDonald and Valenzuela, 2016;Nowotny, 2016;Aure, 2013). Also, language skills, as one of the key factors of a possible improvement of one's position in the labour market, are accentuated (Cerna, 2016;Spoonley, 2006;Sert, 2016;Iguchi, 2012). At the level of individual migrants, over-qualification is caused by their specific migration aims, motives and strategies in the labour market.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, some researchers have also found that host country language level does not play a role in the emplacement of migrants, with the exception of the dwindling NGO and tourism sectors (Garrido and Codó, 2017). Additionally, despite possessing highly valued language skills, even English, qualified migrants with tertiary educational qualifications often still undergo declassing and downward professional mobility (Sert, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A migrant's success in the labour market of the destination country depends on many different factors such as personality, capabilities, and experience of local culture as well as language skills (Nowotny 2016, Cerna 2016, Sert 2016. The migrant's over-qualification is also influenced by the economy of the host country, the level of unemployment, the effect of the current and past economic crisis, the size of the grey economy, and the effectiveness of the administration and related institutions (Eichhorst et al 2017, Cangiano 2014.…”
Section: General Patterns Of International Migration From Ukrainementioning
confidence: 99%